PENGARUH TRANSPARANSI, AKUNTABILITAS, SISTEM PENGENDALIAN INTERNAL, DAN PARTISIPASI TERHADAP PENGELOLAAN DANA DESA - Vullaela Yuliastuti; Arif Hartono; Iin Wijayanti (Gapenas Publisher, 2022)
Village fund management includes planning, implementation, reporting and accountability of village fund. Good management of village funds is expected to bring villages more advanced, productive and prosperous. “The phenomenon of village fund management in Balong district shows that only 40% of villages are able to manage village funds optimally”.”The purpose of this study was to determine the effect of transparency, accountability, internal control system, and participation on village fund management”. “The sampling technique used was total sampling with a sample size of 100 respondents”. “The type of data used in this study is primary data”. “Data collection techniques include questionnaires, documentation and interviews”. “The data analysis technique in this study uses descriptive statistics, validity and reliability tests, classical assumption tests which include normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, t test, F test, and coefficient of determination”. “The results of this study indicate that there is a significant influence between transparency, accountability, internal control, and community participation on the management of village funds in villages in Balong district